(untitled) (Research, Society and Development, 2022)
The question of inclusive education in Brazil is complex and paradoxical, since there is a recommendation in the Federal Constitution (Brazil, 1988) for access to education without discrimination, but the Brazilian schools, especially those of basic education in their majority, are not prepared to receive special students. The present study focuses on education for the surdos. The general objective is to carry out a bibliometric study on this subject, with the time span being the years between 2017 and 2021. Based on the data collected, the Digital Library of Theses and Dissertations (BDTD) was used. Or study is considered as exploratory. The results show that no field of scientific production has a theoretical gap of work originating in the Northeast Region of Brazil. For its time, the theme of education for the left-handed in basic education has been explored in the Southeast Region. Among the selected papers, four dissertations have been cited for our academic productions. Among the themes most worked on in the selected works, the potential for scientific language for left-handed people stands out, as well as the challenges that lie between Libras/Portuguese in bilingual education. The study concluded that there is still a lot of research and production on education for left-handed people in the context of basic education. The gaps in the production of knowledge detected here can encourage the realization of new studies with a view to strengthening the state of the art concerning this theme.